A Fractional-Order Investigation of Vaccinated SARS-CoV-2 Epidemic Model with Caputo Fractional Derivative. (24th March 2022) - Alkahtani, Badr Saad T.
Abstract : In this paper, we consider a fractional-order mathematical system comprising four different compartments for the recent pandemic of SARS-CoV-2 with regard to global and singular kernels of Caputo fractional operator. The SARS-CoV-2 fractional mathematical model is analyzed for series-type solution by Laplace–Adomian decomposition techniques (LADM) and homotopy perturbation method (HPM). The whole quantity of each compartment is divided into small parts, and then the sum of these all parts is written as a series solution for each agent of the system, while the nonlinear part is decomposed using the Adomian polynomial. The model is also checked for approximate solution by HPM through a comparison of the parameter power, p, for each equation. The numerical simulation for both methods is provided in different fractional orders along with comparison with each other as well as with natural order 1.